Marketing Strategies And Food And Beverage Sales At Vila Lumbung - I Putu Dio Oscar Pramudia; Ni Putu Wiwiek Ary Susyarini; I Nyoman Mei Rejeki; Ni Nyoman Triyuni (Jurnal Sains Terapan Pariwisata, 2021)
This study is to identify the strengths and weaknesses of internal factors, to identify opportunities and threats from external factors, and to assess the appropriate strategies to be applied at Vila Lumbung, Bali, Indonesia. Data collection methods used are participant observation, structured interviews, questionnaires and documentation. The analysis techniques used in this study are descriptive qualitative analysis, Internal Factor Analysis Summar (IFAS) Matrix, External Factor Analysis Summary (EFAS) Matrix, Internal-External Matrix (IE), SWOT analysis and Quantitative Strategic Planning Matrix (QSPM) analysis. There are internal and external factors that influence the marketing strategy to increase food and beverage sales which carried out by the sales marketing and F&B staff at the Vila Lumbung. Based on the results of IFAS matrix analysis, the main strength are strategic location and employee hospitality in providing services, while the main weaknesses is complete facilities to support marketing strategies to increase food and beverage sales. Based on the results of the EFAS matrix analysis, it is known that the main opportunity is the hospitality of the local people, while the main threat faced are consumer spending patterns and global economic conditions. The results of the IE Matrix research, show that the company was place in the Growth (Cell V) position. The SWOT analysis resulted in 9 alternative marketing strategies, from that 9 strategies obtained by 3 marketing strategies that were prioritized and were calculated through the QSPM Matrix, with a total TAS 347.50, 315.14, and 307.65.